Posebni instituti davčnega postopka v razmerju do varstva javnega interesa in varstva pravic zavezancev - Špilar, Marjan (visokošolska dela, 2018)
The doctoral thesis with the title "Special institutes of the tax procedure in relation to the public interests protection and the taxpayers right protection" discusses the legal regulation of the tax procedure with an emphasis on the special institutes of the tax procedure which interfere in a very sensitive relationship between private and public benefit and in this way in the collision of interests, while the latter is not absolute and unlimited. The introduction chapters of the doctoral thesis present our administrative procedural system which consists of the rules of general administrative procedure and the rules of special administrative procedures, among which the tax procedure is certainly one of the most demanding and also the most extensive. A number of questions and dilemmas concerning complexity, systematic approach, integrity and wholeness of our tax procedural, respectively, general tax legislation, as also its comparability to foreign legal regulations, are discussed in this part of the doctoral thesis. The selected special institutes of the tax procedure namely, advance tax ruling, self incrimination and tax write-off, deferral and payment in instalments for individuals are discussed in details within the central part (fourth chapter) of the doctoral thesis. The stated institutes are discussed from the aspect of standardisation within the law which might reflect in the protection of the public benefit to an extensive degree by the tax collection, respectively in the insufficient protection of taxpayers' rights with their tax obligations fulfilment. Questions and dilemmas concerning accordance with the principles of the rule of law and other constitutional principles, respectively the extensive interference in the basic constitutional taxpayers' rights appear in respect to some special institutes, as well. A short presentation of some foreign tax procedure institutes which contribute additionally to the transparent and equal relation to taxpayers concerning tax collection and which are not contained in our tax legislation, is the content of the last chapter of the doctoral thesis, as well. The entire topic within the doctoral thesis is discussed from legally theoretical and practical aspect and from domestic and foreign legal practice point of view. However, the regulation of the tax procedure and the special institutes in the neighbour Republic Austria, as also in some other European Union countries, is presented from the legal comparative point of view.
Keywords: davčni postopek; davčni zavezanec; davki; disertacije; fizične osebe; odlog; odpis; posebni instituti; samoprijava; upravni postopek; zavezujoča informacija